If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -77 = 7x + -45 Reorder the terms: -77 + 9x = 7x + -45 Reorder the terms: -77 + 9x = -45 + 7x Solving -77 + 9x = -45 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -77 + 9x + -7x = -45 + 7x + -7x Combine like terms: 9x + -7x = 2x -77 + 2x = -45 + 7x + -7x Combine like terms: 7x + -7x = 0 -77 + 2x = -45 + 0 -77 + 2x = -45 Add '77' to each side of the equation. -77 + 77 + 2x = -45 + 77 Combine like terms: -77 + 77 = 0 0 + 2x = -45 + 77 2x = -45 + 77 Combine like terms: -45 + 77 = 32 2x = 32 Divide each side by '2'. x = 16 Simplifying x = 16
| (3/10)2-1 | | z/32+5/8=13/26 | | 2y^2-4y^3= | | 2(4k+1)+3(5k+1)= | | 4x^2+16xy= | | (20x)-5y=-15 | | 2(4-4)=4-10 | | 1/2(8a^2-10a+7) | | -5x^2+7x-4=0 | | 1250+8%12= | | x+5=2x+0 | | 2(4-x)=x-10 | | x=(3/10)y-1 | | 5x-15/3x-9 | | 8+2x=7x-27 | | -3+x=3x-25 | | 10x-6=66 | | 13q-3q= | | -4x+1=2x-11 | | (x+15)/2=13 | | 6-6x=-5x+0 | | (x^2-6x-16)/(x^2-36) | | -2+3x=2x+9 | | 16/3=32/x | | 45-14b+b^2=0 | | -3/y=-6 | | -12=-3(3x-2) | | 10u+19u= | | 5=-7/y | | h=-16t^2+113t+93 | | -8=-6/y | | 2w^2-5w=42 |